Translation-Strategies Use: A Classroom-Based Examination of Baker’s Taxonomy - Aguado-Giménez, Pilar; Pérez-Paredes, Pascual-Francisco (Meta)

(untitled) (Les Presses de l'Université de Montréal, 2005)
AbstractTeaching translation strategies has become a relevant part of university translation courses. Strategies, such as those outlined by Mona Baker, are useful in different ways. First, they help solve equivalence problems; second, they favour translation-as-a-process awareness and, third, they present students with opportunities to discuss and reflect on contextualized theoretical issues. In this study, the authors set out to explore, in terms of strategy use, English into Spanish translations produced by undergraduate university students (n=160). As a result, Mona Baker’s taxonomy is reviewed and enlarged. Some of the conclusions point out to the fact that translation strategies teaching favours both the quality and the accuracy of the translations. Similarly, a discussion on strategy choice is presented.